Verb Borrowing: The Integration of English Loan Verbs in Yemeni Arabic - Al-Athwary, Anwar A. H. (Jordan Journal of Modern Languages & Literatures, 2023)
This study aims to examine the extent to which English loan verbs are incorporated in Yemeni Arabic (YA) and how they are integrated into the morphosyntactic system of the dialect. About seventy borrowed verbs were collected from different oral and written sources including local TV series and plays, YouTube videos, and followers’ comments on social media. The data analysis drew on Wohlgemuth’s (2009) model of verbal borrowing typology. It was found that YA employs three main strategies in accommodating English loan verbs: 1) direct insertion with root reduction, 2) light verb strategy, and 3) derivative loan verbs. Direct insertion without root reduction is rarely used. While loan verb derivatives represented a non-patterned strategy in Wohlgemuth’s framework, light verb strategy was the most frequent, occurring in 50% of the data. The findings serve as evidence that foreign verbs can be directly borrowed in YA, and the recent verbs borrowed from the IT domain provide much more insight into the various strategies of loan verb integration in the dialect.